Strategies for marketing really new products to the mass market: A text mining-based case study of virtual reality games - Jeffrey C. F. Ho; Xinzhi Zhang (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper reports on a text mining-based case study aimed at determining how virtual reality (VR) games, as examples of really new products (RNPs), market themselves when they are introduced to the mass market. The goal was to examine the marketing foci of RNPs and any subsequent changes over time when the RNPs survive. VR games are a type of RNP offering several unique benefits, such as immersive gameplay and storytelling, which are advanced compared with their earlier counterparts. To examine the marketing foci of VR games, we collected 17,000 pieces of promotional text from a major online gaming marketplace, Steam Store, published from the beginning of the second quarter of 2016 to the third quarter of 2018. We performed text analysis (topic modeling) and found that game marketers paid particular attention to the VR nature of VR games when they first entered the marketplace. However, game content increasingly was emphasized in subsequent quarters. In addition, the marketing foci for VR games seemed to go through an exploratory process, which was not observed among non-VR games in the same period. The results offer insights into how the focus of RNPs' marketing evolves as their newness fades.
Keywords: 650; digital games; latent dirichlet allocation; online marketplace; really new product; text mining; topic modeling